CONTENT AND ORGANIZATION OF PHYSICAL EDUCATION OF STUDENTS ON THE BASIS OF INVOLVEMENT IN THE VALUE POTENTIAL OF PHYSICAL CULTURE AND SPORTS (Physical Culture and Sport: Scientific Perspective, 2024)
The article deals with the peculiarities of involving students in the potential values of physical education and sports in the professional training of future specialists in physical education and sports. The main direction of involvement in the values of physical education and sports is a systematic approach that involves students in practical activities to master the values of physical education and sports, which forms their awareness of the values and qualities that allow them to live and develop in harmony with the values of personal culture and society. The highest level of students' mastery of the potential values of physical education and sports is participation in physical education and sports activities, which acts as a daily reference point and contributes to the formation of the need for daily physical activity. The theoretical significance of the study lies in the scientific demonstration of the cultural approach to physical education in higher education. This approach complements the theoretical and methodological physical education of students with knowledge about the effective use of means and methods of physical education and the pedagogical conditions necessary for the purposeful involvement of students in the values of physical culture and sports. The necessity of systematic physical education and sports for healthy and harmonious human development and the importance of involving students in the values of physical education and sports as a factor that guarantees participation in them have been theoretically and experimentally established. The practical significance lies in the fact that educational technologies that involve students in the established values of physical culture and sports provide a holistic view of effective ways to solve the problems of upbringing, education, development and health promotion. Curricula focused on involving students in the values of physical culture and sports have been implemented, providing a new approach to the process of physical education in higher education institutions. During the period of reforming the Ukrainian education system, practical recommendations were developed for use in the practical activities of teachers of sports disciplines and as scientific and methodological resources for students and teachers of physical education.
Keywords: values of physical culture; active involvement of students; pedagogical technology; principles of selection; culture of movements; culture of health; culture of physique; aesthetic orientation